(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Fundamentals of the human problem in the history of religious philosophy take their roots from ancient mythological eras, religious beliefs in the east of the religion of the Ancient Age and the religious philosophy of the Middle Ages. After that, the differences between religious philosophy and the philosophy of religion were determined, as well as the directions of research relating to man. The case study required us first of all to determine the versatile formulation of the problem of man in philosophy, after this continuation in elucidating the directions in religion relating to man, then systematizing the doctrines of faith and theological teachings and at the point of their contact clarifying the directions of research on the human problem in the philosophy of religion. The problem of philosophical comprehension of one’s being always occupied man. Questions about what a person is, what are its nature and essence, place and purpose in the world, have great ideological, philosophical and practical significance, since they touch upon the fundamental aspects of human existence, the meaning and purpose of life. That is why a person’s problem can be classified as a philosophical problem that has never been removed and can not be removed from the agenda, for the process of knowing man and the world is infinite and will never be completed. This problem is updated with the course of history, as the person himself, as well as the set of conditions and the content of his life, his goals, ideals and prospects constantly changes. The human problem is always topical in the sense that in every epoch it retains its fundamental meaning and, entering into the content of all significant philosophical systems, means not just the continuation of a certain tradition, but first of all – the identification of the aspects changing with each epoch and the historical perspectives of the human Being. Key words: Philosophy, religion, human, spirituality, moral qualities.